A semelhança de figuras no ensino da geometria plana Vitória - Bachir, Monica de Figueiredo (2017)
This work consists in carrying out an in - depth study on the similarity of flat figures, from a previous knowledge of the basic concepts of flat geometry. In addition to the theory, addressed in the first three chapters and addressed mainly to teachers of mathematics, there are also, in the following three chapters, exercises solved traditionally and also solved using GeoGebra software, in addition to proposed exercises along with their respective expected answers.